The phraseology of administrative French : a corpus-based study - Anderson, Wendy J. (Language and computers, 2006)
The French administrative language of the European Union is an emerging discourse: it is only fifty years old, and has its origins in the French administrative register of the middle of the twentieth century, but it is also a unique contact situation in which translation has always played a pivotal role. Using the methodology of corpus linguistics, and a specially compiled corpus of texts, covering a range of genres, this book describes the current discourse of EU French from the perspective of phraseology and collocational patterning, and in particular in comparison with its French national c.